Economic sanctions and American diplomacy - Haass, Richard, 1951- 1951- (A Council on Foreign Relations book, 1998)
""Sanctions don't work" is an often-heard refrain. The reality, though, is more complex. Sanctions - mostly economic but also political and military penalties aimed at states or other entities to alter political and/or military behavior - almost always have consequences, sometimes desirable, at other times unwanted and unexpected. What cannot be disputed is that economic sanctions are increasingly at the center of American foreign policy: to stem the proliferation of weapons of mass destruction, promote human rights, discourage aggression, protect the environment, and thwart drug trafficking." "Drawing on eight case studies - China, Cuba, Haiti, Iran, Iraq, Libya, Pakistan, and the former Yugoslavia - this edited volume presents lessons to be learned from recent American use of economic sanctions. It also provides specific guidelines designed to shape future decisions by Congress and the executive branch."--BOOK JACKET.